Factors Influencing the Intention to Use GrabPay Among Malaysians - Shashi Gupta; Majdi Anwar Quttainah; Guan Hong Wong; Chiu Yin Wee; YiYe Wang; Shu Ting Wang (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2022)
This research study is about Malaysians view and their intention to use GrabPay. There are four variables selected in this research: perceived usefulness, perceived ease of use, perceived security, and social influence. A total of 100 questionnaires were distributed online to the respondents, and the data were analyzed using SPSS software. Through research, we found that these four variables are positively associated with the intention to use GrabPay among Malaysians. To conclude, it is believed that Malaysian's intention to use E-Wallet is gradually increasing. Thus, GrabPay needs to pay more attention to its security system, expand its service coverage, and make some optimization and simplifications on its application to strengthen its future status. Keywords: Factors, GrabPay, Intention to Use, Malaysians